ANALISIS PENGARUH KUALITAS LAYANAN INTI DAN KUALITAS LAYANAN PERIPHERAL TERHADAP KEPUASAN NASABAH (Studi Pada PT. Bank Negara Indonesia (Persero) Tbk. Cabang Undip Semarang) - Fitria Puspitasari; Suryono Budi Santoso (JURNAL STUDI MANAJEMEN ORGANISASI, 2013)
This study aims to determine how big the influence of core service quality and peripheral service quality to consumer satisfaction on BNI Undip Semarang. The problem that facing by BNI Undip Semarang is consumer’s satisfaction which decreasing, as seen from a lot of complains received from consumer. And this research also aims to analyze the most dominant factors that influence on consumer satisfaction of BNI Undip Semarang. Population of this research are consumers of BNI Undip Semarang. Samples were taken of 100 respondents by using non-probability sampling technique with accidental sampling  approach. Data was collected by using a survery method through quetionnaires which were filled out by consumers. Then, the obtained data were analyzed using multiple regression analysis. This analysis includes: validity test,reliability test, classic assumption test, multiple regression analysis, hypothesis testing through the t test and F test, and coefficient of determination analysis (R²). From the analysis result, the indicators in this study are valid and reliables. The most dominant factor that influence on consumer satisfaction is peripheral service quality follow by the core service quality. Then though the F Test can be seen that the independent variables feasible to test the dependent variable. The result of Adjusted R Square is 36,2%, it means that independent variable can explain about 36,2% of dependent variable. Key word         : core service quality, peripheral service quality, and consumer satisfaction